Leveraging water, sanitation and hygiene for nutrition in low‐ and middle‐income countries: A conceptual framework. Issue 3 (14th May 2021) - Zavala, Eleonor; King, Shannon E.; Sawadogo‐Lewis, Talata; Roberton, Timothy
Abstract: In low‐ and middle‐income countries (LMICs), access to water, sanitation and hygiene (WASH) is associated with nutritional status including stunting, which affects 144 million children under 5 globally. Despite the consistent epidemiological association between WASH indicators and nutritional status, the provision of WASH interventions alone has not been found to improve child growth in recent randomized control trials. We conducted a literature review to develop a new conceptual framework that highlights what is known about the WASH to nutrition pathways, the limitations of certain interventions and how future WASH could be leveraged to benefit nutritional status in populations. This new conceptual framework will provide policy makers, program implementors and researchers with a visual tool to bring into perspective multiple levels of WASH and how it may effectively influence nutrition while identifying existing gaps in implementation and research.